Engineering Catalyst Layers for Next‐Generation Polymer Electrolyte Fuel Cells: A Review of Design, Materials, and Methods. Issue 37 (26th August 2021) - Suter, Theo A. M.; Smith, Keenan; Hack, Jennifer; Rasha, Lara; Rana, Zahra; Angel, Gyen Ming A.; Shearing, Paul R.; Miller, Thomas S.; Brett, Dan J. L.
Abstract: Polymer electrolyte fuel cells (PEFCs) are a promising replacement for the fossil fuel–dependent automotive and energy sectors. They have become increasingly commercialized in the last decade; however, significant limitations on durability and performance limit their commercial uptake. Catalyst layer (CL) design is commonly reported to impact device power density and durability; although, a consensus is rarely reached due to differences in testing conditions, experimental design, and types of data reported. This is further exacerbated by aspects of CL design such as catalyst support, proton conduction, catalyst, fabrication, and morphology, being significantly interdependent; hence, a wider appreciation is required in order to optimize performance, improve durability, and reduce costs. Here, the cutting‐edge research within the field of PEFCs is reviewed, investigating the effect of different manufacturing techniques, electrolyte distribution, support materials, surface chemistries, and total porosity on power density and durability. These are critically appraised from an applied perspective to inform the most relevant and promising pathways to make and test commercially viable cells. This holistic view of the competing aspects of CL design and preparation will facilitate the development of optimized CLs, especially the incorporation of novel catalyst support materials. Abstract : Polymer electrolyte fuel cells (PEFCs) require significant improvements to durability and performance to achieve widespread commercial success. The role of the catalyst layer (CL) in maximizing performance, improving durability, and reducing costs is often overlooked. This review critically appraises the cutting‐edge research involving PEFCs catalyst layers, to facilitate the development of high‐performing CLs via novel materials, manufacturing techniques, and designs.